Pentingnya Pendidikan Karakter dan Rohani Berdasarkan Ulangan 6:6–7 pada Anak Usia 4–6 Tahun di ICHAMPS Kota Wisata (Lembaga Pengembangan Kinerja Dosen, 2025)
Character and spiritual education are essential to shape children’s personality and spirituality from the beginning of their lives. Beliefs and morality can be instilled in children aged 4 to 6 years old, when they are in the golden age of development. The purpose of this study was to determine the importance of character and spiritual education according to Deuteronomy 6:6–7 at ICHAMPS Kota Wisata, a Christian educational institution. These verses show how important it is for adults to tell others about God’s word every day. This study was conducted using a descriptive qualitative approach. Data were collected through observation, in-depth interviews with teachers and parents, and documentation of learning activities. The results showed that character and spiritual education at ICHAMPS were integrated through activities such as Bible stories, group prayers, teacher examples, and fun worship rituals. Children gradually showed an understanding and internalization of values ​​such as respect, love, honesty, and responsibility. Families and schools collaborated actively, which was essential for success. However, there were some challenges, such as time constraints and the influence of the external environment. This study showed that education based on God’s word was consistently very effective in shaping children’s character at an early age. Therefore, parental involvement should be increased, and teachers should be trained to use contextual and relevant approaches.